The concept and practice of teacher education at the Jagiellonian University with respect to new standards - Kowalczyk, Dorota (Przegląd Badań Edukacyjnych (Educational Studies Review), 2014)
The article attempts to describe the state of teacher education at the Jagiellonian University after the introduction of the new standards of preparation for teaching. The concept of teacher education proposed in the College of Education at the Jagiellonian University is based on methodological assumptions of constructivism and the concept of reflective practice and the purpose of meeting and collaboration of faculty and students is to prepare for the teaching profession in such a way that agraduate undertaking work, on the one hand, represents high professional competence, (to complement the knowledge gained in the home institute) and on the other, consciously pursues a certain ethical standard of an educator. The decision to take the course in the College of Education at the Jagiellonian University is the issue of individual, informed choice. Therefore, at the College of Education, students can individually decide when to pursue a course, on which days and hours to attend classes. The essence of the candidate's preparation at the College lies in psycho-pedagogical education to perform the role of the teacher. The course covers the knowledge and skills in terms of psychology and pedagogy, in accordance with Regulation of the Minister of Science and Higher Education of 17.01.2012 on the standards of education in preparation for the teaching profession. Classes on subject didactics in parent institutes, and internships carried out in schools under the supervision of their employees are an integral part of the curriculum of the College of Education and fall within the scope of the duty in the course of pedagogical preparation training. Students receive the certificate of graduation from the College of Education after graduation from applicable studies. This creates the possibility of adopting a different program of action by the student in accordance with their own assumptions, taking full responsibility for the decisions taken.